Trends and Prospects of Education and Upbringing of Young Generation in Uzbekistan during the Years of Independence - et. al., Zukhra Karabaevna Ismailova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article covered scientific and pedagogical aspects of the state policy, its priorities, essence and essence of the education of young generation in Uzbekistan in the years of independence, as well as the use of modern pedagogical and information and communication technologies and the Internet, scientific and technical information.